Use of carbonised beet pulp carbon for removal of Remazol Turquoise Blue-G 133 from aqueous solution - Dursun, Arzu Y.; Tepe, Ozlem; Dursun, Gulbeyi (Springer Heidelberg, 2013)
Carbonised beet pulp (BPC) produced from agricultural solid waste by-product in sugar industry was used as adsorbent for the removal of Remazol Turquoise Blue-G 133 (RTB-G 133) dye in this study. The kinetics and equilibrium of sorption process were investigated with respect to pH, temperature and initial dye concentration. Adsorption studies with real textile wastewater were also performed. The results showed that adsorption was a strongly pH-dependent process, and optimum pH was determined as 1.0. The maximum dye adsorption capacity was obtained as 47.0 mg g(-1)at the temperature of 25 A degrees C at this pH value. The Freundlich and Langmuir adsorption models were used for describing the adsorption equilibrium data of the dye, and isotherm constants were evaluated depending on sorption temperature. Equilibrium data of RTB-G 133 sorption fitted very well to the Freundlich isotherm. Mass transfer and kinetic models were applied to the experimental data to examine the mechanisms of adsorption and potential rate-controlling steps. It was found that both external mass transfer and intra-particle diffusion played an important role in the adsorption mechanisms of dye and adsorption kinetics followed the pseudo second-order type kinetic model. The thermodynamic analysis indicated that the sorption process was exothermic and spontaneous in nature.
Keywords: Adsorption; Carbonisation; Beet pulp carbon; Remazol Turquoise Blue-G 133; Kinetics; Intra-particle diffusion model; External mass transfer model